CompTIA security+ SY0-301 exam cram - Barrett, Diane (Exam cram., 2012)
Prepare for CompTIA Security+ SY0-301 exam success with this CompTIA Authorized Exam Cram from Pearson IT Certification, a leader in IT Certification learning and a CompTIA Authorized Platinum Partner. CompTIA® Security+ Exam Cram , Third Edition, is the perfect study guide to help you pass CompTIA's newly updated version of the Security+ exam. It provides coverage and practice questions for every exam topic. The book contains a set of 200 questions in two full practice exams. Limited Time Offer : Buy CompTIA Security+ SY0-301 Authorized Exam Cram and receive a 10% off discount code for the CompTIA Security+ SYO-301 exam. To receive your 10% off discount code: Register your product at pearsonITcertification.com/register Follow the instructions Go to your Account page and click on "Access Bonus Content" The CD-ROM contains the powerful Pearson IT Certification Practice Test engine that provides real-time practice and feedback with all the questions so you can simulate the exam. Covers the critical information you need to know to score higher on your Security+ exam! Master and implement general security best practices Systematically identify threats and risks to your systems Harden systems by eliminating nonessential services Secure your communications, networks, and infrastructure Systematically identify and protect against online vulnerabilities Implement effective access control and authentication Create security baselines and audit your security infrastructure Understand cryptographic principles, and effectively deploy cryptographic solutions Organize security from both a technical and organizational standpoint Manage every facet of security, including education and documentation Understand the laws related to IT security, and the basics of forensic investigations Kirk Hausman (CISSP, CISA, CRISC, Security+) has worked as an ISO, consultant, trainer, and IT director. He is Assistant Commandant for IT at TAMU and teaches InfoSec topics as an Adjunct Professor at UMUC and UAT. Martin Weiss (CISSP, CISA, Security+, MCSE) leads a team of information security experts at Symantec supporting solutions to provide confidence in a connected world. Diane Barrett (CISSP, MCSE, A+, Security+) is the director of training for Paraben Corporation and an adjunct professor for American Military University. Companion CD The CD-ROM contains two, complete practice exam. Includes Exclusive Offer for 70% Off Premium Edition eBook and Practice Test Pearson IT Cert...